Two unpublished letters between Manuel García Morente and Xavier Zubiri - Infante Gómez, Juan Carlos (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
We hereby present two unpublished letters exchanged between the philosophers Manuel García Morente and Xavier Zubiri. The first letter, written by the Andalusian philosopher, sheds light on his religious conversion, which led him to become a Catholic priest. The aforesaid conversion had begun to take shape the previous year in Paris; both philosophers were in exile in the French capital, right after the outbreak of the Spanish Civil War. In the second letter, dated almost two and a half years later, Zubiri addressed a few endearing words to the Andalusian philosopher, in response to Morente’s invitation to attend his first Mass. In that letter, the Basque philosopher revealed their unbreakable friendship, which had been intensified by their Christian faith in recent years.
Keywords: García Morente; Xavier Zubiri; reason and faith; intellectual process of religious conversion; relegation